2012
DOI: 10.1039/c2jm15991k
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured BiMnO3+δ obtained at ambient pressure: analysis of its multiferroicity

Abstract: International audienceThe BiMnO3+delta phase has been prepared by mechanosynthesis, at ambient pressure and room temperature, as nanocrystalline powders. This oxide exhibits a metastable character, similar to those prepared by high-pressure and high-temperature methods, remaining stable up to 673 K. Nanostructured ceramic materials (92% densification), maintaining the BiMnO3+delta composition, have been successfully processed by the spark plasma sintering technique, at the very low temperature of 673 K, in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
(99 reference statements)
2
26
0
Order By: Relevance
“…Ferromagnetic order of the Mn 3+ at the B-site develops at 100 K, while ferroelectric offcenter distortion would be driven by the stereochemically active Bi +3 lone pair at the A-site [44]. However, later detailed structural characterizations, electrical measurements down to 77 K, and studies of the lattice dynamics have shown this oxide not to be ferroelectric [45][46][47]. This is consistent with studies of the xBiMnO 3 -(1 -x)PbTiO 3 solid solution that clearly indicated the disappearance of ferroelectricity for x ≥ 0.5 [48].…”
Section: I31 Single-phase Multiferroicsmentioning
confidence: 99%
“…Ferromagnetic order of the Mn 3+ at the B-site develops at 100 K, while ferroelectric offcenter distortion would be driven by the stereochemically active Bi +3 lone pair at the A-site [44]. However, later detailed structural characterizations, electrical measurements down to 77 K, and studies of the lattice dynamics have shown this oxide not to be ferroelectric [45][46][47]. This is consistent with studies of the xBiMnO 3 -(1 -x)PbTiO 3 solid solution that clearly indicated the disappearance of ferroelectricity for x ≥ 0.5 [48].…”
Section: I31 Single-phase Multiferroicsmentioning
confidence: 99%
“…53 Subsequent additional neutron diffraction experiments confirmed this space group determination, 44 but an independent report using SAED indicated the presence of long-ranged monoclinic C2 order, in coexistence with short ranged P2 or P2 1 distortions, and thus, of a polar state. 54 The length of the short range order seems to increase with the oxygen hyperstoichiometry, 39 but a P2 1 /c space group has been determined for BiMnO 3:08 . 44 Further insight into this issue can only be gained by a sound electrical characterization, which requires the processing of high quality ceramics.…”
Section: Revisiting Bimnomentioning
confidence: 99%
“…39 Oxygen hyperstoichiometry was controlled by XPS and magnetic measurements, by comparing the N eel temperature of 80 K to previous reports on the evolution of the magnetism with stoichiometry. 44 A composition of BiMnO 3:04 was estimated, so monoclinic C2/c phase can be assumed.…”
Section: Revisiting Bimnomentioning
confidence: 99%
See 2 more Smart Citations